Social Impacts of the Socio-Environmental Disaster Caused by BRASKEM S.A. in Maceió, Alagoas - Fragoso, Amanda Carolina Simões; Gonçalves, Rafael Soares (National Journal of City Management, 2024)
This article aims to discuss the social impacts of the socio-environmental disaster caused by Braskem S.A.’s salt mining activities in Maceió, AL. The study was conducted through a literature review. Testimonies from residents were identified in reports, articles, and academic works, as well as in newspaper reports (print and electronic media, both written and video formats). The article also incorporates the firsthand experience of the first author, a resident of the city and directly affected by the disaster. The text analyzes the social and emotional damages to displaced populations and residents in areas impacted by land subsidence caused by the underground collapse of the mines. Numerous social impacts were identified, including the loss of property and income, the closure of public facilities, the disruption of social bonds, and the emergence of emotional problems. The case should be considered a socio-environmental crime of significant impact, raising questions about possible forms of economic and social reparations involving the Maceió population, both directly and indirectly.